Hydrogen sulfide aggravates neutrophil infiltration, vascular remodeling and elastase-induced abdominal aortic aneurysm in male mice - Clémence Bechelli; Diane Macabrey; Florian Caloz; Severine Urfer; Martine Lambelet; Florent Allagnat; Sébastien Déglise (Communications Medicine)
Abstract Background Abdominal aortic aneurysm (AAA) has an 80% mortality rate upon rupture, with no pharmacological treatments available to slow its progression. Hydrogen sulfide (H₂S), produced by cystathionine γ-lyase (CSE), has anti-inflammatory and antioxidant properties, but its role in AAA remains unclear. Methods We evaluated the impact of sodium thiosulfate (STS), a clinically relevant H₂S donor, in a periadventitial elastase-induced AAA model in normotensive male wild-type and Cse−/− mice. Complementary in vitro studies were conducted on primary human vascular smooth muscle cells (VSMCs) to assess the effects of STS on proliferation, senescence and cytokine-induced apoptosis. Results Contrary to expectations, STS dose-dependently aggravate AAA progression by increasing extracellular matrix degradation. Although STS reduces macrophage and lymphocyte infiltration, it enhances neutrophil accumulation, particularly MMP9⁺ neutrophils, and promotes the formation of c-KIT⁺-MPO⁺ pre-neutrophil clusters. Cse−/− mice show reduced neutrophil infiltration and smaller aneurysms, supporting a pathogenic role of endogenous H₂S. STS also impairs VSMC proliferation and induces senescence, blunting compensatory aortic remodeling. Conclusions H₂S, delivered via STS, exacerbates AAA progression under normotensive conditions by promoting neutrophil-driven inflammation and impairing VSMC repair. These findings challenge the assumption that H₂S is universally protective in vascular disease and raise caution regarding the therapeutic use of STS in patients at risk for AAA.